Obesity: transition from adolescence to adulthood and feedback partial gmm logistic model with time-dependent covariates (Epidemiology, Biostatistics, and Public Health, 2022)
Background: The aim of this study is to investigate the impact of certain covariates on obesity. More importantly, we seek to determine the feedback of obesity on depression, and physical activity as they transition from adolescence to young adulthood.Methods: Using 15 years of nationally representative data from 6560 adolescents (Add health data), we estimate feedback and associations between depression, and activity scale on obesity while we adjusted for gender, age, race/ethnicity, socioeconomic status through a GMM logistic regression model with time-dependent covariates.Results: Activity (p